Sinyal Bahaya Demokrasi Pascaputusan MK tentang Batas Usia Minimum Capres dan Cawapres (Analisis Perbincangan Warganet di X) - Pambudi, Buyung; Prajarto, Nunung; Irawanto, Budi (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2024)
This research stems from Mahkamah Konstitusi’s decision to change the electoral constitution when the election stage was already underway. Netizens then discussed the decision of the Majelis Kehormatan Mahkamah Konstitusi (MKMK) which decided that the chairman of the Constitutional Court violated the code of ethics when hearing the election constitutional lawsuit. The election organizer (KPU RI) also did not escape the discussion of netizens after being decided to violate the code of ethics by Dewan Kehormatan Penyelenggara Pemilu (DKPP). The conversations of netizens on X/Twitter regarding the Chief Justice of the MK, MKMK, and the Chairman of the KPU were collected using NodeXL, then described in the form of tables and descriptions. The communication network analysis method was chosen as a data analysis tool. X/Twitter was used as a means of expressing opinions and disseminating information related to the 2024 elections. Netizens' conversations about the Chief Justice of the MK, MKMK, and the Chairman of the KPU signal the danger of democracy in Indonesia.